Tradisi Menenggetti: Sebuah Refleksi Teologi Pengharapan Jurgen Moltmann Bagi Perempuan Pakpak - Berutu, Icca (NABISUK : Jurnal Teologi dan Pelayanan, 2024)
The aim of this research is to describe people's perceptions regarding the menenggetti tradition and to find out Jurgen Moltman's theological reflection on the hopes contained in menenggetti. This research uses qualitative research methods using two approaches, literature study and interviews. The community's view of menenggetti is that it is a tradition of menenggetti carried out by parents for the beru they love who have been married for a long time but do not have children, menenggetti as a place to pray and ask for offspring to be given to their beru, the food brought during menenggetti is only an intermediary for God's blessings to descend upon them. family. The results of this research indicate that the expectations contained in menenggetti reflect the expectations expressed by Jurgen Moltmann